Women Veterans' Experiences with Integrated, Biopsychosocial Pain Care: A Qualitative Study. Issue 9 (6th February 2021) - Nicosia, Francesca M; Gibson, Carolyn J; Purcell, Natalie; Zamora, Kara; Tighe, Jennifer; Seal, Karen H
Abstract: Objectives: Biopsychosocial, integrated pain care models are increasingly implemented in the Veterans Health Administration to improve chronic pain care and reduce opioid-related risks, but little is known about how well these models address women veterans' needs. Design: Qualitative, interview-based study. Setting: San Francisco VA Health Care System Integrated Pain Team (IPT), an interdisciplinary team that provides short-term, personalized chronic pain care emphasizing functional goals and active self-management. Subjects: Women with chronic pain who completed ≥3 IPT sessions. Methods: Semistructured phone interviews focused on overall experience with IPT, perceived effectiveness of IPT care, pain care preferences, and suggested changes for improving gender-sensitive pain care. We used a rapid approach to qualitative thematic analysis to analyze interviews. Results: Fourteen women veterans (mean age 51 years; range 33–67 years) completed interviews. Interviews revealed several factors impacting women veterans' experiences: 1) an overall preference for receiving both primary and IPT care in gender-specific settings, 2) varying levels of confidence that IPT could adequately address gender-specific pain issues, 3) barriers to participating in pain groups, and 4) barriers to IPT self-management recommendations due to caregiving responsibilities. Conclusions: Women veterans reported varied experiences with IPT. Recommendations to improve gender-sensitive pain care include increased provider training; increased knowledge of and sensitivity to women's health concerns; and improved accommodations for prior trauma, family and work obligations, and geographic barriers. To better meet the needs of women veterans with chronic pain, integrated pain care models must be informed by an understanding of gender-specific needs, challenges, and preferences.